2019
DOI: 10.1002/slct.201803828
|View full text |Cite
|
Sign up to set email alerts
|

Grown Carbon Nanotubes on Electrospun Carbon Nanofibers as a 3D Carbon Nanomaterial for High Energy Storage Performance

Abstract: Carbon hierarchical nanostructures have been widely applied because of their outstanding properties and large surface area. Future energy materials for applications, such as Li‐ion, Li‐sulfur, Li‐air batteries, and supercapacitors require materials with high energy density and power capability. The preparation of three‐dimensional (3D) carbon nanotubes (CNTs)‐carbon nanofibers (CNFs) nanomaterials through a multi‐step process has many difficulties. The aggregation, the high expense of CNTs, and the difficult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 145 publications
(199 reference statements)
0
8
0
Order By: Relevance
“…CNTs are wrapped into cylinder tubes by graphene layers through sp 2 bonds that hold the carbon atoms into an aromatic ring structure. 26,27 Such a well-defined structure with the strong π-electron interaction results in outstanding electrical capacitance and intriguing quantum effects of CNTs. 27 Recent research has demonstrated that using CNTs as the carbon support in electrocatalysis provides synergistic interactions with metal catalysts and thus improves catalytic activity and selectivity.…”
Section: Background Of Cnts and Their Applications In Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…CNTs are wrapped into cylinder tubes by graphene layers through sp 2 bonds that hold the carbon atoms into an aromatic ring structure. 26,27 Such a well-defined structure with the strong π-electron interaction results in outstanding electrical capacitance and intriguing quantum effects of CNTs. 27 Recent research has demonstrated that using CNTs as the carbon support in electrocatalysis provides synergistic interactions with metal catalysts and thus improves catalytic activity and selectivity.…”
Section: Background Of Cnts and Their Applications In Electrocatalysismentioning
confidence: 99%
“…26,27 Such a well-defined structure with the strong π-electron interaction results in outstanding electrical capacitance and intriguing quantum effects of CNTs. 27 Recent research has demonstrated that using CNTs as the carbon support in electrocatalysis provides synergistic interactions with metal catalysts and thus improves catalytic activity and selectivity. 28,29 To date, many M@CNTs have been engineered into high-efficiency electrocatalysts in a range of electrocatalytic reactions such as ORR, water-splitting reactions, CO 2 RR, and NRR.…”
Section: Background Of Cnts and Their Applications In Electrocatalysismentioning
confidence: 99%
“…[1] Based on the GCD curves, the areal capacitance of the hierarchical VACNTs electrode are calculated by formula (3) and the value is ≈1300 mF cm −2 , which is higher than most reported carbon-based SCs (Table 1). [13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] In addition, the specific capacitance can also be obtained by means of CV curve integration, namely Equation (4).…”
Section: Electrochemical Performance Of Hierarchical Vacnts-based Scmentioning
confidence: 99%
“…g) Rate performance test of the Al micro grid-based VACNT SC from 13 to 91 mA cm −2 . h) A comparison of Al micro grid-based VACNT SC with other carbon-based SC reported in literature [22][23][24][25][26]. i) Performance comparison of laser-etched Al-based VACNTs SC with other carbon materials SCs reported in literature[27][28][29][30][31] .…”
mentioning
confidence: 99%
“…In the late 1990s, the attention in this method has increased. Up to now, the publications′ number in the field of electrospinning has been increasing dramatically because of its ability to produce fibers with small diameters, ease of functionality, high specific surface area, good pore structures, flexibility, low density, excellent mechanical properties, extraordinary adjustability, and encouraging applications in different fields such as biomedical applications, energy harvesting, sensors, tissue engineering, self‐cleaning surfaces, catalyst, filtration, fuel cells applications, biological applications, food packaging applications, water treatment field, and so on.…”
Section: Introductionmentioning
confidence: 99%